The Case Against Harry Dexter White : Still Not Proven - Boughton, James (IMF Working Papers; Working Paper, 2000)
Harry Dexter White, the principal architect of the international financial system established at the end of the Second World War, was arguably the most important U. S. government economist of the 20th century. His reputation, however, has suffered because of allegations that he spied for the Soviet Union. That charge has recently been revived by the declassification of documents showing that he met with Soviet agents in 1944 and 1945. Evaluation of that evidence in the context of White's career and worldview casts doubt on the case against him and provides the basis for a more benign interpretation.